Inositol 1,4,5-trisphosphate-induced release of sequestered Ca2+ from highly purified human platelet intracellular membranes. - Authi, K S (1985)
Evidence has accumulated in support of a role for intracellularly generated inositol 1,4,5-trisphosphate [Ins(1,4,5)P3] in raising cytosol [Ca2+] when various hormones, neurotransmitters, growth factors and other stimulants act on cell surfaces. The increase in [Ca2+] that follows stimulant-receptor interaction is accompanied by rapid hydrolysis of phosphoinositides. One product, Ins(1,4,5)P3, arising from the breakdown of phosphatidylinositol 4,5-bisphosphate was shown to promote the release of Ca2+ from non-mitochondrial stores in a variety of cells. Although platelet intracellular membranes have been implicated in the control of cytosol [Ca2+] and we previously characterized a Ca2+-sequestering mechanism associated with them, we have as yet no knowledge of how this Ca2+ store is mobilized after a stimulus-receptor interaction at the platelet surface. Using free-flow electrophoresis, we isolated and purified human platelet intracellular membranes. They show high enrichment and exclusive localization of the endoplasmic-reticulum marker NADH:cytochrome c reductase, and they sequester Ca2+ by an ATP-dependent process, reaching steady-state values in 10-12 min. Saturation with Ca2+ occurs at around 10-30 microM external Ca2+. When Ins(1,4,5)P3 is added to the 45Ca-loaded vesicles, a rapid release of Ca2+ occurs (approx. 35% in 15-30s). The magnitude of the release depends upon external [Ca2+], being maximum in the range 0.3-0.8 microM and low at external [Ca2+] greater than 1 microM. After release there is a rapid re-uptake of Ca2+, with restoration of the former steady-state values within 1 min. Half-maximal release occurs at approx. 0.25 microM-Ins(1,4,5)P3. This release and re-uptake pattern is not observed with ionophore A23187 or arachidonic acid, both of which liberate Ca2+ irreversibly. Inositol 1,4-bisphosphate was ineffective in releasing Ca2+ from these intracellular membranes. The results support the role of Ins(1,4,5)P3 as a specific intracellular mediator, transducing the action of excitatory agonists acting on the platelet surface into metabolic, mechanochemical and other functional events, known to occur during platelet activation.